Control of pathogenic and spoilage microorganisms from cheese surface by whey protein films containing malic acid, nisin and natamycin - Pintado, C.S. (2022)
The inhibitory effects of nisin, natamycin and malic acid, incorporated in whey protein films with pH 3, were investigated alone or with addition of sucrose esters, Tween80 or EDTA. Water vapour permeability measurements and mechanical and rheological tests were also assessed. EDTA and Tween80 did not significantly (P < 0.05) influence the inhibitory activity of films against Pseudomonas aeruginosa and Yarrowia lipolytica in contrast with the improved effect against Listeria monocytogenes, Penicillium commune and Penicillium chrysogenum. Sucrose esters reduced significantly (P < 0.05) the inhibitory effect for Y. lipolytica and Penicillium spp. The present work provides an antimicrobial film formulation with potential to be a hurdle against spoilage and pathogenic microorganisms isolated from cheese surface.